Genetic characterization of intramuscular myxomas - William John Hatchett; Marta Brunetti; Kristin Andersen; Maren Randi Tandsæther; Ingvild Lobmaier; Marius Lund-Iversen; Thomas Lien-Dahl; Francesca Micci; Ioannis Panagopoulos (Frontiers Media S.A., 2024)
Introduction: Intramuscular myxomas are benign tumors that are challenging to diagnose, especially on core needle biopsies. Acquired chromosomal aberrations and pathogenic variants in codon 201 or codon 227 in GNAS complex locus gene (GNAS) have been reported in these tumors. Here we present our genetic findings in a series of 22 intramuscular myxomas.Materials and methods: The tumors were investigated for the presence of acquired chromosomal aberrations using G-banding and karyotyping. Pathogenic variants in codon 201 or codon 227 of GNAS were assessed using direct cycle Sanger sequencing and Ion AmpliSeq Cancer Hotspot Panel v2 methodologies.Results: Eleven tumors carried chromosomal abnormalities. Six tumors had numerical, four had structural, and one had both numerical and structural chromosomal aberrations. Gains of chromosomes 7 and 8 were the most common abnormalities being found in five and four tumors respectively. Pathogenic variants in GNAS were detected in 19 myxomas (86%) with both methodologies. The detected pathogenic variants were p.R201H in nine cases (seven with abnormal and two with normal karyotypes), p.R201C in five cases, all with normal karyotypes, p.R201S in three cases (two with abnormal and one with normal karyotype), p.R201G in one case with a normal karyotype, and p.Q227E in one case with a normal karyotype.Conclusion: Firstly, our data indicate a possible association between chromosomal abnormalities and GNAS pathogenic variants in intramuscular myxomas. Secondly, the presence of the rare pathogenic variants R201S, p.R201G and p.Q227E in 26% (5 out of 19) of myxomas with GNAS pathogenic variants shows that methodologies designed to detect only the common "hotspot" of p.R201C and p.R201H will give false negative results. Finally, a comparison between Ion AmpliSeq Cancer Hotspot Panel v2 and direct cycle Sanger sequencing showed that direct cycle Sanger sequencing provides a quick, reliable, and relatively cheap method to detect GNAS pathogenic variants, matching even the most cutting-edge sequencing methods.